2018
DOI: 10.31254/phyto.2018.7602
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and proximate composition of root, stem bark, leaf and fruit of desert date, Balanites aegyptiaca

Abstract: Balanites aegyptiaca or Desert date is a common plant in all dry lands of Africa and South Asia. Some parts of the plant are used as fish poisons but not poisonous to man. It is also used as medicine or food in humans as well as insect repellent. Four parts of the plant were phytochemically and proximately screened to determine whether the bioactive compounds can be utilized in sedation or anaesthetization of fish as well as supplementation of fish nutrition. The root, stem bark, leaf and fruit of the plant we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…It was slightly similar to the observations of Henna et al ( 2010), who reported the presence of the same phytochemicals in the AE-BAF except steroids and alkaloids were not detected in their study. This is in line with other phytochemical study of Wakawa et al (2018), who demonstrated the same in the AE-BAF, except cardiac glycosides and alkaloids were not detected in their study.…”
Section: Discussionsupporting
confidence: 92%
“…It was slightly similar to the observations of Henna et al ( 2010), who reported the presence of the same phytochemicals in the AE-BAF except steroids and alkaloids were not detected in their study. This is in line with other phytochemical study of Wakawa et al (2018), who demonstrated the same in the AE-BAF, except cardiac glycosides and alkaloids were not detected in their study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this could be caused by reasonable differences in the electrochemically active substances in different plant leaves. Plant leaves can have certain differences in their chemical composition because of the different light areas received [19], the different heights of growth [20], etc. It can be seen from the electrochemical fingerprint that all species exhibited oxidation peaks in the anodic scan, which was caused by the oxidation of some electrochemically active substances, such as flavonoids and polyphenols [21,22], in leaf tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The tip of leaves of Talinum triangulare is obtuse compared with T. paniculatum. The petal color of T. triangulare is darker and larger in size than T. paniculatum [4].…”
Section: Introductionmentioning
confidence: 87%
“…One milliliter of the extract was taken and diluted with 1 mL of distilled water. The sample contains saponins if the foam is present after shaking [4]. The absorbance was measured by a spectrophotometer at 435 nm [11].…”
Section: Methodsmentioning
confidence: 99%